Regulatory Compliance of Health Claims on Omega-3 Fatty Acid Food Supplements - Jelena Banović Fuentes; Ivana Beara; Ljilja Torović (Foods)
Unlike the mandatory information that must be provided on a food supplement label, health claims are voluntary. This study assesses the regulatory compliance of omega-3 fatty acid (ω-3-FA) supplement label claims. Of the 97 supplements, 76 (78.4%) carried verbal claims referring to active substance, of which 68 (89.5%) were claims specific to ω-3-FA. According to the European Union Health Claims Registry, 107 claims listed on 59 supplements were authorized, as opposed to nine unauthorized claims on nine supplements. The degree to which claims aligned with regulatory standards, expressed in terms of scores scaled from 0 to 1, was the highest for supplements intended for pregnant women (1), while, in the case of adults, the mean score was 0.76 ± 0.35, and, in case of children, was 0.85 ± 0.27. Statistical analysis revealed a minor tendency for higher health claim scores to be associated with lower product prices. Furthermore, differences in compliance levels across groups of supplements formed according to the country of origin/sources of ω-3-FA/target populations were explored. The main differences were associated with products from Sweden and Italy/fish oil/supplements for pregnant women. A comparison of the daily intake of ω-3-FA provided by the supplement (based on labeled information) with the intake requirements for supplements with claims referring to ω-3-FA, supported 91 claims, five were unsubstantiated, and 11 were missing required data. Supplements also contained mineral- (19 approved) and vitamin-related claims (73, of which 9 were unauthorized). This study’s findings reveal the extent of misuse of labelled information in markets that require pre-market supplement registration. Importantly, the non-compliance of health claims can significantly undermine consumer trust.